Seabed images from deep-sea sponge aggregations in the Faroe-Shetland Channel Nature Conservation Marine Protected Area - Georgios Kazanidis; Johanne Vad; Lea-Anne Henry; Francis Neat; Barbara Berx; Konstantinos Georgoulas; J Murray Roberts (PANGAEA, 2019)
In this data set, we provide environmental (coordinates, depth, temperature, salinity, type of substrate, demersal fisheries) and biological data (sponge morphotype density and sponge morphotype size) from seabed images collected using a towed camera in the sponge belt located in the Faroe-Shetland Channel Nature Conservation Marine Protected Area.
In: Kazanidis, G et al. (2019): Seabed images and corresponding environmental data from deep-sea sponge aggregations in the Faroe-Shetland Channel Nature Conservation Marine Protected Area [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.897604